Thai-German Research Project WADIS Recommendations for the investigation of Abandoned and Proposed Waste Disposal Sites in Thailand - Lietz, Juergen (Frontiers in Engineering Innovation Research, 2003)
Many waste disposal sites in Thailand are sources of environmental pollution because domestic as well as industrial waste has been largely disposed of in the past without effective safety and control measures. The Thai-German Research project "WADIS" is jointly carried out by the Department of Mineral Resources (DMR) and the Federal Institute for Geosciences and Natural Resources (BGR) The project focuses on the risk assessment of abandoned waste sites as well as on the Multi- Barrier- Concept for the selection of new waste disposal sites. The Multi - Barrier-Concept includes besides technical barrier (made by man) also the natural rocks below a waste site as an important barrier and safety system against contaminant spreading and groundwater pollution. The WADIS Project has so far selected two abandoned waste sites near Chiang Mai as pilot sites for the exemplary investigation of their geological and hydrological setting and for risk assessment. The surveys comprise geological, geophysical, hydrogelogical and laboratory investigations supported by drilling of groundwater monitoring wells. Know-how and technology transfer as well as the provision of a handbook for site investigations are major objectives of the project.